Application and developing of iron‐doped multi‐walled carbon nanotubes (Fe/MWCNTs) as an efficient and reusable heterogeneous nanocatalyst in the synthesis of heterocyclic compounds. (9th November 2017) - Sharghi, Hashem; Aboonajmi, Jasem; Mozaffari, Mozhdeh; Doroodmand, Mohammad Mahdi; Aberi, Mahdi
Abstract : Iron‐doped multi‐walled carbon nanotubes (Fe/MWCNTs) is an efficient, ecofriendly and reusable heterogeneous nanocatalyst for the one‐pot synthesis of heterocyclic compounds including bis‐spiro piperidines, piperidines, dihydro‐2‐oxopyrroles, pyrazoles and diazepines at room temperature with good to excellent yields. The heterogeneous nanocatalyst was fully characterized by scanning electron microscopy (SEM), X‐ray diffraction (XRD), inductively coupled plasma (ICP) and FT‐IR analysis. Also, the structures of all prepared compounds were characterized by 1 H NMR, 13 C NMR, FT‐IR, mass spectrometry (MS) and elemental analysis. The major advantages of these protocols are mild and green reaction conditions, short reaction times, clean reaction, operational simplicity, easy purification and good to excellent yields with the reusable heterogeneous nanocatalyst. The catalyst was ten recycled without significant loss of activity. Abstract : Iron‐doped multi‐walled carbon nanotubes (Fe/MWCNTs) is an efficient, ecofriendly and reusable heterogeneous nanocatalyst for the one‐pot synthesis of heterocyclic compounds including bis‐spiro piperidines, piperidines, dihydro‐2‐oxopyrroles, pyrazoles and diazepines at mild conditions with good to excellent yields. The heterogeneous nanocatalyst was fully characterized. The major advantages of these protocols are mild and green reaction conditions, short reaction times, clean reaction, operational simplicity, easy purification and good to excellent yields. The catalyst was ten recycled without significant loss of activity.